Analisis Perubahan Perilaku Konsumen Terhadap UMKM di Cifest Cikarang Selatan Selama Periode Libur: Studi Kasus Pembelian Online Vs. Offline - Pradipta Rizky Ferdian; Rois Kurniawan; Muhammad Kosim; Delima Pebrianti Salsabil; Reni Anggraeni; Ryan Akbar Maulana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
In recent years, Micro, Small, and Medium Enterprises (MSMEs) have increasingly positioned themselves as one of the main pillars of the Indonesian economy, contributing significantly to employment opportunities, income distribution, and economic resilience. In the local context, Cifest Cikarang Selatan represents a dynamic marketplace where various MSMEs operate and directly interact with consumers. An interesting phenomenon emerges during holiday periods, when consumer behavior shows significant changes, especially in terms of purchasing methods and preferences between online and offline channels. This study aims to explore the transformation of consumer behavior, focusing on the comparative analysis of online and offline purchases, and to evaluate its broader implications for the sustainability and competitiveness of MSMEs operating at Cifest. The research adopts a descriptive and analytical approach, using both recent statistical data and supporting literature to provide a comprehensive understanding of the digital era’s influence on shopping patterns. The findings reveal that online purchases continue to grow rapidly due to convenience, wider product access, and promotional offers that attract customers. However, offline purchases remain relevant, particularly for consumers who value direct product inspection, immediate ownership, and social interaction within traditional marketplaces. For MSMEs, this shift presents both challenges and opportunities. Those that rely solely on conventional offline strategies risk losing competitiveness, while those able to integrate digital platforms with traditional sales methods demonstrate greater adaptability and potential for growth. Overall, this study concludes that the sustainability of MSMEs in Cifest Cikarang Selatan depends largely on their ability to embrace digital transformation without neglecting the strengths of offline interactions. By leveraging both channels strategically, MSMEs can not only survive but also thrive in the increasingly competitive market landscape shaped by evolving consumer behavior.